Cyclical antiidiotypic response to anti-hormone antibodies due to neutralization by autologous anti-antiidiotype antibodies that bind hormone (The Rockefeller University Press, 1983)
Antiidiotype antibodies were raised against anti-catecholamine ligand antibodies. The antiidiotype response was shown to be cyclical and to correspond to the production of antibodies that could bind to catecholamine beta-adrenergic receptors and stimulate adenylate cyclase. Disappearance of these antibodies from the serum could be correlated with the appearance of a catecholamine ligand-binding activity corresponding to the synthesis of autologous anti-antiidiotype antibodies directed against the induced antiidiotypic molecules. Comparison of the injected versus the induced anti-ligand antibodies reveals striking differences in affinities but similarities in the ability to bind to the antiidiotype antibodies and to the ligand- containing affinity gel. The results support the existence of a functional network of idiotype antiidiotype interactions involving external as well as internal antigens, antibodies, and possibly other types of molecules involved in recognition phenomena, such as hormone receptors.